Effects of perceived spiritual management, work engagement, and organizational commitment on job satisfaction among clinical nurses: the mediating role of perceived spiritual management - Eun-Hye Lee; Hea-Jin Yu (BMC Nursing, 2023)
Abstract Background Spirituality in the workplace has a positive impact on organizations. It strengthens employees’ well-being and their quality of life. It also gives work a sense of purpose and meaning and creates a sense of interconnectedness. Methods This study is a descriptive cross-sectional survey which intends to determine how job satisfaction is impacted by spiritual management, work engagement, and organizational commitment from the perspective of clinical nurses. Responses to self-administered questionnaires were collected from 230 hospital nurses in South Korea from July to August, 2022. Results Job satisfaction was positively correlated with perceived spiritual management (r = .662), job commitment (r = .514), and organizational commitment (r = .587). Perceived spiritual management had the highest correlation with job satisfaction, followed by organizational commitment and job commitment. To determine the effect of these factors on clinical nurses’ job satisfaction, a hierarchical multiple regression analysis-in other words, a method that controls the entry order of a series of independent variables-was conducted. Model 4 ultimately explained 58.4% of job satisfaction (R2 = 0.584; F = 44.563; p < .001), with an additional 2.5 explained variance. Among the control variables in Model 4, only marital status (β = 0.173) was positively significant; perceived spiritual management (β = 0.388), work engagement (β = 0.208) and organizational commitment (β = 0.225) were all found to have significant positive effects on job satisfaction. The mediation analysis showed that perceived spiritual management had a partial mediating effect on the relationship between work engagement, organizational commitment, and job satisfaction. Conclusion The results of this study confirm that job satisfaction for nurses requires not only individual predispositions, but also active changes in management strategies, such as spirituality management at the hospital’s organizational level.